Melodic Literacy: Enhancing Word Recognition Through the Singing Method - Theresia Ninu Amaunut Neon Beni; Hendrawan Armanto (Murhum : Jurnal Pendidikan Anak Usia Dini, 2026)
Word recognition is a key foundation of early literacy. However, many children still find it difficult to connect speech sounds, or phonemes, with written symbols, or graphemes. This study aimed to improve word recognition skills in children aged 5–6 years through a singing method. The study employed a collaborative Classroom Action Research (CAR) design conducted in two cycles. Data were collected from 22 children through participatory observation and performance-based assessment. The main novelty of this study lies in the use of repeated melodies and rhythms as mnemonic tools to help children link the sounds of words with their written forms. The findings showed a significant improvement in children's word recognition skills. At baseline, only 9% of the children reached the Developing as Expected (BSH) level. After the intervention in Cycle I, this percentage increased to 81.8%. By the end of Cycle II, 95.5% of the children had reached the Very Well Developed (BSB) level, while the remaining 4.5% had reached the BSH level. These results indicate that the singing method is effective in reducing children's affective barriers, such as anxiety and lack of confidence, while also strengthening long-term vocabulary retention. Therefore, this study offers a practical framework for educators to implement interactive, multisensory literacy strategies that support children's holistic cognitive development.